Influence of Blending Method and Blending Ratio on Ring-spun Yarn Quality – a MANOVA Approach - Jamal Hossen; Subrata Kumar Saha (Tekstilec)
Cotton-polyester is a common and popular fibre blend in the textile industry nowadays. Its main advantage is that it improves the functional properties of clothing and textile products. In this study, fibre-blended, sliver-blended and roving-blended yarns with a fineness of 23 tex were manufactured using a ring spinning system, with blend ratios of cotton and polyester fibres of 50:50, 60:40 and 70:30. The quality parameters of the produced yarn, such as mass variations, imperfections, hairiness and bundle yarn strength, were studied. The end breakage rate of the ring frame machine was also studied during the manufacturing of the yarns. The results were analysed using multivariate analysis of variance (MANOVA) to determine the significance of the impact of the blending method and blending ratio on yarn quality and the end breakage rate of the ring frame machine. The profile plots were analysed from statistical and technical points of view. Among the three blended yarns, fibre-blended yarn demonstrated the best results in terms of mass variations and imperfections due to better blending homogeneity, while roving-blended yarn demonstrated better results in terms of hairiness. Among the blended yarn, fibre-blended yarn demonstrated the highest bundle yarn strength value, while the corresponding end breakage rate of the ring frame machine recorded the lowest value. The yarn quality was improved in terms of mass variations, imperfections, hairiness and bundle yarn strength by increasing the polyester fibre percentage in the blend ratio.